On the agora : the evolution of a public space in Hellenistic and Roman Greece (c. 323 BC - 267 AD) - Dickenson, Christopher P. (Mnemosyne, Supplements, 2016)
On the Agora traces the evolution of the main public square of the Greek polis for the six centuries from the death of Alexander the Great in 323 BC to the height of the Roman Empire and the Herulian invasion of Greece in 267 AD. Drawing on literary, epigraphic and, especially, archaeological evidence, the book takes a comparative approach to consider how the layout and function of agoras in cities throughout Greece changed during centuries that witnessed far reaching transformations in culture, society and political life. The book challenges the popular view of the post-Classical agora as characterised by decline, makes important arguments about how we use evidence to understand ancient public spaces and proposes many new interpretations of individual sites.